Women's Rights and Gender Equality - Noormawati (Sharia Journal and Education Center Publishing, 2024)
AbstractWomen's rights and gender equality, especially in the current generation, face a lot of pros and cons due to the increasing number of women pursuing their careers, especially against older generations who speculate that women's duty is only at home, serving their husbands. They are not allowed to enter the workforce, politics, or even governance.This research utilizes a descriptive method through literature review of journals, websites, and books obtained via Google Scholar containing information regarding women's rights and gender equality from various perspectives including the four schools of thought, scholars, and societal views.The aim is for students to have a broad understanding and perspective on various third-party viewpoints in responding to current issues, enabling them to analyze and have a comprehensive view in addressing issues related to women's rights and gender equality incorporating various perspectives from the four schools of thought in addressing these issues and the various societal views regarding women's involvement in politics, social affairs, governance, and the workforce to pursue careers, especially in the current generation, which inevitably sparks controversy among scholars regarding gender issues between women and men. Additionally, there are societal views, particularly from older generations, that still hold a patriarchal perspective towards women. The Quran asserts in its verses the equality of men and women in terms of their rights, status, dignity, and humanity, both in terms of devotion and in terms of law.Keywords : right, patriarchy, gender equalityAbstrakHak-hak perempuan dan kesetaraan gender khususnya pada generasi sekarang karena banyaknya perempuan yang ingin mengejar karirnya menuai banyak pro dan kontra didalamnya, terlebih lagi terhadap golongan tua yang berspekulasi bahwa perempuan tugasnya hanya di rumah dan melayani suami saja. Tidak diperkenankan untuk memasuki dunia pekerjaan, politik bahkan pemerintahanPenelitian ini menggunakan metode deskripsi melalui tinjauan literatur jurnal, website dan buku yang didapat melalui google scholar yang memuat informasi-informasi berkenaan tentang hak-hak perempuan dan kesetaraan gender berbagai perspektif empat Mazhab, para ulama hingga pandangan masyarakat di dalamnya.Yang bertujuan agar mahasiswa/i dapat mengetahui atau berpandangan luas melihat berbagai pandangan sudut ketiga dalam menanggapi permasalahan yang terjadi pada masa sekarang agar dapat menelaah dan dapat berpandangan luas dalam menanggapi isu-isu suatu permasalahan mengenai hak-hak perempuan dan kesetaraan gender yang memuat berbagai perspektif dari empat Mazhab dalam menanggapi permasalahan ini dan adanya berbagai pandangan di masyarakat terkait hak perempuan yang berkecimpung dalam urusan politik, urusan sosial, pemerintahan hingga dalam dunia pekerjaan untuk mengejar karir terutama generasi saat ini yang tentunya menimbulkan banyak kontroversial antar para ulama tentang permasalahan gender antara perempuan dan laki-laki. Juga adanya pandangan masyarakat khususnya golongan tua yang masih berpandangan